(untitled) (Journal of Engineering, 2024)
Recently, some of Iraq’s newly constructed asphalt concrete pavements showed premature failures with significant negative impacts on roadway safety and the economy. Using Nano hydrated lime (NHL) in pavement construction could be one of the possible steps to improve pavement durability. This article discusses how NHL affects the durability of hot mix asphalt. NHL was added in two methods to the asphalt concrete mixture for the wearing course. The first is the dry method, i.e., on the aggregate, whereas the second is the wet addition method, i.e., to the bitumen. The percentages were tried for each additional method; 1, 2, and 3% by weight of aggregate for the dry method and 0.5, 1, and 1.5% by weight of asphalt concrete for the wet method. The optimum asphalt cement contents were evaluated using the Marshall procedure. Asphalt concrete mixes were prepared at their optimum asphalt content and then tested to evaluate their durability properties, including moisture damage and permanent deformation. These properties have been evaluated using indirect tensile strength and uniaxial repeated loading tests. The results show that the NHL has improved the permanent deformation characteristics and resistance to moisture susceptibility.